Perjury by Omission - Ira P. Robbins (Washington University Law Review, 2019)
“Do you swear to tell the truth, the whole truth, and nothing but the truth?” There are few legal phrases that the layperson can repeat verbatim; this is one of them. But how many people truly understand the nuances and ramifications of testifying under oath? Many assume that if they do not provide the “whole truth” under oath, they will face a perjury charge. However, perjury is a charge often threatened but rarely used. The offense requires that the defendant willfully and knowingly make a false statement, under oath, regarding a material fact. The federal perjury statute does not contemplate a scenario in which a defendant (or declarant, deponent, witness, or interviewee) withholds truthful information in an attempt to mislead the questioner and alter the outcome of a judicial proceeding—in sum, not telling the “whole truth.” But, in Bronston v. United States, the Supreme Court considered just this situation, holding that the language of the federal perjury statute does not contemplate a defendant who intentionally omits material information. Instead, the Court broadly ruled that “literally truthful” answers are categorically forbidden from being the basis of perjury. The Court placed the burden on the questioner to elicit the desired answer from a witness when confronted with a literally truthful, yet unresponsive and misleading answer. Such an onus suggests that all questioners possess the abilities of a mind reader. This Article demonstrates that the Bronston Court created unforeseen consequences. Currently, a sophisticated defendant can dodge a perjury charge by providing a literally true answer while omitting pertinent information. Sometimes, these answers communicate a lie, but as long as they are literally truthful under the Bronston Court’s broad interpretation, a defendant could never face a perjury charge. Congress can fill the holes of this decision by amending the federal perjury statutes to criminalize those who intentionally give incomplete or misleading responses regarding material information under oath.
Keywords: Perjury; Criminal law; Bronston v. United States 409 U.S. 352 (1973); Omission; Literal truth; Ethics; Federal perjury